Commute to school, level of physical activity, and physical fitness of young adolescents in the Municipality of Florestal, Minas Gerais - de Oliveira, Jennifer (2018)
This study aimed to evaluate performance in physical fitness tests and physical activity level when comparing the level of physical activity and performance in physical fitness tests among adolescents who moved in three different ways to school.The sample was 60 students (50% female), divided equally into three groups: walk, bike and motorized transport, aged between 15 and 18 years (16,38 ±0,86 years). The physical fitness was evaluated by means of the six-minute run/walk tests, horizontal jump test and 20m maximal speed run. The physical activity score was estimated by the brief IPAQ version. The time and distance displaced by each school was estimated through the Global Positioning System by the Google Maps application. The main findings were that in the physical fitness evaluation, in neither test and for both sexes were found significant differences in physical performance of the three groups. But we found differences in physical activity levels between the walking and motorized transport groups. And the distance traveled by the motorized group was higher than that of the other groups, in both sexes, and the mean total time spent to perform the displacement in the bicycle group in both sexes was smaller. The differences in time or distance between the groups were not able to produce an e ect on the physical fitness. We concluded that the walking group presents a higher level of physical activity to the other groups, pedaling and motorized, suggesting that walking improves physical tness due to time spent on the course.